Enhancing Critical Thinking Skills through Project-Based Chemistry Practicum Using Seaweed Hydrogel Design - Dulanlebit, Yeanchon Henry; Hernani, Hernani; Liliasari, Liliasari; Amran, Muhammad Bachri (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study explores the effectiveness of a project-based chemistry practicum in enhancing critical thinking and conceptual understanding among chemistry teacher candidates. Using a seaweed-based hydrogel as a medium for adsorbing metal ions, the practicum incorporates contextual learning processes, including problem investigation, collaborative engagement, and technology design. Conducted with 36 students at Pattimura University, the study applied a mixed-methods approach, combining qualitative observations and quantitative data analysis. Results indicate significant improvements in students' critical thinking, as evidenced by an N-Gain of 0.72, enhanced worksheet scores, and better practicum outcomes. The findings underscore the importance of integrating environmental resources and technological tools in practicum activities to foster creativity and innovation. However, the study highlights the need for adequate laboratory resources, extended practicum time, and advanced rubrics to assess complex learning outcomes effectively. These insights contribute to the development of advanced chemistry practicum models that align with 21st-century learning skills.